Synthesis, Characterization and Evaluation of Some Meldrum’s Acid Derivatives as Lubricant Additives - Hussien, Hadeel A.K; Al-Messri, Zainab A. K. (Iraqi Journal of Science, 2023)
Aminomethylene Meldrum’s acid derivatives were synthesized by a three-component, one-pot reaction of Meldrum’s acid with triethyl orthoformate and different aromatic amines. The prepared compounds were characterized using Fourier transform infrared (FT-IR), nuclear magnetic resonance (1H NMR and 13C NMR) and evaluated as anti-corrosion and anti-rust additives by blending with base lubricating oil, according to the American Society of Testing and Materials (ASTM-D130 and ASTM-D665). The blends of the synthesized compounds with the base lubricating oil showed better anti-rust and anti-corrosion effects than the base oil Blank).